Mechanistic Profiling of Novel Wafer Technology Developed for Rate-Modulated Oramucosal Drug Delivery - Patel, Rupal (My University, 2006)
A lyophilized polymeric wafer system was formulated for the provision of rapid drug release in the oramucosal region. Lyophilization produced a porous sponge-like matrix which allowed simulated saliva to be rapidly imbibed into the hydrophilic structure. This surge of simulated saliva resulted in rapid disintegration of the wafer. Hydroxypropyl cellulose (HPC) was selected as the polymeric platform based on its low gelation potential. Other excipients incorporated into the system were lactose and mannitol as diluents, and glycine as a collapse protectant. A Face Centred Central Composite Design was chosen to establish the significant effects of the independent formulation variables on the physicochemical and physicomechanical properties of the wafer. The formulation variables investigated were, HPC concentration, type of diluent (lactose, mannitol or mixture), concentration of diluent, quantity of glycine and fill volume. An analysis of these variables elucidated the influential factors that may be controlled to form an ‘ideal’ wafer. The concentration of HPC significantly affected the disintegration rate (p=0.003), influx of simulated saliva (p=0.011) and friability (p=0.023). The quantity of diluent present in the system also had significant effect on matrix tolerance (p=0.029) and friability (p=0.032). Statistical optimization was undertaken using stepwise forward and backward regression, and Artificial Neural Networks to predict the ideal combination of the independent variables that would produce an ideal formulation. This wafer was required to produce a matrix disintegration of 3.33%/s, friability of 0.1% loss and maximum matrix resilience. Formulations manufactured with and without model drug, diphenhydramine hydrochloride, reflected no significant differences in their physicomechanical and physicochemical properties. In an attempt to expand the scope of this technology, a preliminary investigation was undertaken to develop a prolonged release wafer system. This was successfully achieved trough the application of crosslinking technology. It was possible to achieve drug released over a period of 6 hours.
Student Number ; 9901384G - MPharm dissertation - School of Pharmacy and Pharmacology - Faculty of Health Sciences
Keywords: oramucosal drug delivery; rapid drug delivery; textural analysis; wafer; polymers; hydroxy propyl cellulose